Hepatitis-B-associated glomerular disease : a clinicopathological study of Hepatitis B virus associated Membranous Glomerulonephritis in Namibian and South African children 1974 - 2005 and a comparison with Hepatitis B associated Membranous Glomerulonephritis as well as Idiopathic Membranous Glomerulonephritis in adults - Bates, William D. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2011.